The Proto-Atmosphere of Terrestrial Planets - Liu, Lin-gun (European Journal of Applied Sciences, 2025)
The theoretically derived composition of the proto-atmosphere, which evolved during accretion, of terrestrial planets is composed primarily of CO2, Ar and N2 when the mass of a planet became greater than 3.30 x 1026 g. This is identical to the atmospheric compositions of Venus and Mars observed today. Therefore, both Venus and Mars most likely retained their proto-atmospheres till now. The Earth is situated between Venus and Mars, there is no reason whatsoever that the Earth’s proto-atmosphere should be any different from those of Venus and Mars. Yet, today’s Earth atmospheric composition is drastically different from her proto-atmosphere. Mercury is not massive enough to hold even CO2 to form a proto-atmosphere. Therefore, Mercury is virtually in vacuum. A “magma ocean” has been proposed to commence and cover the surface of the Earth when her radius grew over ~2550 km. All H2O in the primordial planetesimals would dissolve in the “magma ocean” during accretion. Thus, H2O would never be one of the proto-atmospheric components even if the mass of terrestrial planets was over 8.06 x 1026 g. Any significant amount of H2O on the surface of all terrestrial planets must be added or derived via other mechanisms after the completion of accretion. The Earth’s hot and soda indigenous ocean of supercritical H2O-CO2 mixture was most likely derived from the giant impacting process that produced the Moon. It is this ocean that removed all CO2 from the Earth’s proto-atmosphere.